Application System Document Submission to Improving Services in Jedongcangkring Village, Prambon District Web-Based - Muhammad Fadil Santoso; Arif Senja Fitrani (Indonesian Journal of Cultural and Community Development, 2021)
One of the problems faced by the Jedongcangkring village government, Prambon sub-district, is the process of submitting village documents in making or submitting manual letters, where this has an impact on services that are less than optimal for Jedongcangkring village residents, Prambon sub-district. During this Covid-19 pandemic, information technology is needed by humans in carrying out various human jobs. A computer is a device that was created to facilitate human work, while achieving rapid progress both in terms of hardware and software. The use of Microsoft Word, Excel, Outlook, and other office software in making letters has several weaknesses, such as dependence on high village administrative capabilities resulting in letter formats often changing and prone to inaccuracies in recording data from letters that have been made. With this web-based village village document submission application, it is hoped that it can solve the problems that are being faced by Jedongcangkring village, Prambon sub-district in carrying out correspondence activities and improving correspondence administration services to be better.